Acetylshikonin isolated from Lithospermum erythrorhizon roots inhibits dihydrofolate reductase and hampers autochthonous mammary carcinogenesis in Δ16HER2 transgenic mice. (November 2020) - Wang, Junbiao; Iannarelli, Romilde; Pucciarelli, Stefania; Laudadio, Emiliano; Galeazzi, Roberta; Giangrossi, Mara; Falconi, Maurizio; Cui, Lishan; Navia, Aleix Marti; Buccioni, Michela; Marucci, Gabriella; Tomassoni, Daniele; et al.
Graphical abstract: Abstract: Breast cancer (BC) is the most common cancer in women and, among different BC subtypes, triple negative (TN) and human epidermal growth factor receptor 2 (HER2)-positive BCs have the worst prognosis. In this study, we investigated the anticancer activity of the root ethanolic and hexane extracts from Lithospermum erythrorhizon, a traditional Chinese herbal medicine known also as tzu ts'ao or tzu-ken, against in vitro and in vivo models of TNBC and HER2-positive BC. Treatment with L. erythrorhizon root extracts resulted in a dose-dependent inhibition of BC cell viability and in a significant reduction of the growth of TNBC cells transplanted in syngeneic mice. Acetylshikonin, a naphthoquinone, was identified as the main bioactive component in extracts and was responsible for the observed antitumor activity, being able to decrease BC cell viability and to interfere with autochthonous mammary carcinogenesis in Δ16HER2 transgenic mice. Acetylshikonin anticancer effect depends on its ability to act as a potent inhibitor of dihydrofolate reductase (DHFR), to down-regulate key mediators governing cancer growth and progression, such as HER2, Src and STAT3, and to induce apoptosis by caspase-3 activation. The accumulation of acetylshikonin in blood samples as well as in brain, kidney, liver and tumor tissues was also investigated by liquid chromatography coupled with tandem mass spectrometry (LC–MS/MS) highlighting that L. erythrorhizon treatment is effective in delivering the active compound into the target tissues. These results provide evidence that L. erythrorhizon extract and in particular its main component acetylshikonin are effective against aggressive BC subtypes and reveal new acetylshikonin mechanisms of action.